Line 22:
Line 22:
== squreroot ==
== squreroot ==
Suppose N is a natural number such that N=<math> M^2 </math> . The number M is called square root of M
Suppose N is a natural number such that N=<math> M^2 </math> . The number M is called square root of M
−
we have <math>m^2</math>=mxm or (-m)x(-m)=<math>(-m)^2</math> thus <math>m^2</math> has 2 squer roots, m;m and m example 9=<math>3^2</math> or <math>(-3)^2</math>.thus both 3 and -3 or <math>\sqrt9</math>
+
we have <math>m^2</math>=mxm or (-m)x(-m)=<math>(-m)^2</math> thus <math>m^2</math> has 2 square roots, m;m and m example 9=<math>3^2</math> or <math>(-3)^2</math>.thus both 3 and -3 or <math>\sqrt9</math>
[[File:square number.png|200 px|centre]]
[[File:square number.png|200 px|centre]]